A multi-stimuli-responsive metallohydrogel applied in chiral recognition, adsorption of poisonous anions, and construction of various chiral metal-organic frameworks - Xu, Xuebin; Xiao, Jiannan; Liu, Meiying; Liu, Zhiliang (Chemical communications (Cambridge, England), 2019)
The design of stimuli-responsive hydrogels is attractive but challenging. A multi-stimuli-responsive chiral metallohydrogel was constructed using a rational approach to design a functional metallohydrogel using chiral organic gelators. The as-synthesized metallohydrogel reported here performed remarkably as a visual sensor for discriminating between ( R )-phenylglycinol and ( S )-phenylglycinol. Furthermore, the metallohydrogel showed a significant capacity for adsorption and enrichment of Cr( vi ) in aqueous solution. Besides this, by utilizing anion-induced transformation, the metallohydrogel could be controllably directed to synthesize different types of chiral metal-organic frameworks. A multi-stimuli-responsive chiral metallohydrogel applied to chiral recognition, adsorption of poisonous anions, and construction of various chiral metal-organic frameworks.